TRANSFORMASI PEMBELAJARAN SOSIOLOGI: PERAN KETERAMPILAN 4C DI ABAD KE-21: Indonesia - Mahendra, Yoga; Mulyawan, Galuh; Putri, Vina Karina (IKIP Siliwangi Bandung, 2023)
The development of education and the transformation of 21st-century learning have influenced the shift in the educational paradigm in preparing learners who are adaptable to the challenges of the times. Unlike other scientific fields, especially sociology, which aims to explore various events or phenomena that emerge in society. Therefore, this article aims to critically examine the transformation of sociology learning through the role of the 4C skills in the 21st century. This research employs a qualitative method with a descriptive analysis approach and gathers information through literature review. The research findings indicate that the role of the 4C skills in the 21st century can be considered an alternative in sociology learning, which can be internalized by changing the conventional